'Top-Down' holmium laser enucleation of the prostate. Report of initial cases performed by a single surgeon. Issue 2 (3rd April 2021) - Hodhod, Amr; Oquendo, Fabiola; Tablowski, Thomas; Abdul-Hadi, Ruba; Shahrour, Walid; Kotb, Ahmed; Prowse, Owen; Elmansy, Hazem
ABSTRACT: Objectives: To present the 12-month outcomes of 'Top-Down' holmium laser enucleation of the prostate (HoLEP). Patients and methods: We retrospectively reviewed the charts of prospectively collected patients who underwent Top-Down HoLEP between 2017 and 2018. All cases were operated upon by a single urologist (H.E), using a 100-W holmium:YAG laser with a 550-μm laser fibre. We recorded the enucleation time, morcellation time, intraoperative, and postoperative complications. All patients had postoperative follow-up visits at 1, 3, 6 and 12 months. The evaluation included the International Prostate Symptom Score (IPSS), quality-of-life (QoL) assessment, measurement of maximum urinary flow rate (Qmax ) and the post-void residual urine volume (PVR). Results: A total of 60 consecutive patients were recruited. The median (range) prostatic volume, resected prostatic weight, and percentage of resected prostatic tissue were 124 (70–266) mL, 90 (44–242) g and 76 (46–97)%, respectively. The median (range) enucleation and morcellation times were 80 (25–200) and 14.5 (4–58) min, respectively. One patient had a simple bladder mucosal injury and another developed clot retention. At 3 months, three patients (5%) had stress urinary incontinence (SUI) and eight patients (13.3%) presented with urge UI (UUI). At the last follow-up visit, one patient (1.7%) presented with persistent SUI, while three patients (5%) presented with UUI. The IPSS and QoL significantly improved during the follow-up period ( P = 0.045 and P = 0.04, respectively). Conclusion: The results of the Top-Down technique are comparable to those of traditional HoLEP. However, the Top-Down technique may reduce the complexity, operating time, and SUI rates. Abbreviations: BN: bladder neck; HoLEP: holmium laser enucleation of the prostate; PVR: post-void residual urine volume; Qmax : maximum urinary flow rate; QoL: quality of life; TOV: trial of voiding; (S)(U)UI: (stress) (urge) urinary incontinence